ANALISIS TINGKAT KAPITALISASI PROPERTI SEKTOR PERUMAHAN (STUDI RUMAH MEWAH DI KABUPATEN SLEMAN, 2014) - , Panji Kusuma P, Dr. Akhmad Makhfatih, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research is to analyze capitalization rate of luxuriant house in Sleman District and its influential factors. In this research will be analized the central tendency (mean) of capitalization rate for overall region and also for each regions. For the second objective, a few factors will be analyzed, are they statiscally signifiant influence the luxuriant house capitalizaion rate in research area. A few factor that will be analyzed are asses of the building, lot size, location, and age of the building. This research uses cross section data only from the prime source through stratified sampling, which over 5 regions of luxuriant housing complex in Sleman District are Bale Agung, Bale Hinggil, Pondok Permai Kaliurang, Hyarta and Pesona Merapi, using 50 sample data. The empirical result of this analyzed show that the mean value capitalization rate of luxuriant house in research area is 4,029 percent. From the result of regression analyzed can be known which variables or factors that statistically significant influence the capitalization rate of luxuriant house in research area, the result show us that the assess of the building, lot size, location, and age of the building are statistically significant influence the capitalization rate of luxuriant house in research area. Empirical Model in this research has explanation power 60 percent.